Autophagy controls mesenchymal stem cell therapy in psychological stress colitis mice. Issue 9 (2nd September 2021) - Tian, Jun; Kou, Xiaoxing; Wang, Runci; Jing, Huan; Chen, Chider; Tang, Jianxia; Mao, Xueli; Zhao, Bingjiao; Wei, Xi; Shi, Songtao
ABSTRACT: Mesenchymal stem cell transplantation (MSCT) has been applied to treat a variety of autoimmune and inflammatory diseases. Psychosocial stress can aggravate disease progression in chronic inflammatory patients. Whether psychological stress affects MSCT is largely unknown. In this study we show that psychological stress attenuates therapeutic effects of MSCT in a DSS-induced colitis mouse model by elevating the levels of exosomal Mir7k/mmu-let-7 k (microRNA 7 k) in circulation. Mechanistically, Mir7k inhibits STAT3 pathway in donor MSCs, leading to upregulated expression of BECN1 (beclin 1, autophagy related) and, thus, activation of macroautophagy/autophagy. Inhibition of autophagy by blocking Mir7k or activating STAT3 signaling can restore MSCT-mediated therapy in psychologically stressed colitis mice. Our study identifies a previously unknown role of autophagy in regulating MSCT therapy via exosomal miRNA Mir7k . Abbreviations: BafA1: bafilomycin A1 ; BECN1: beclin 1, autophagy related; DAI: disease activity index; DAPI: 4ʹ, 6-diamidino-2-phenylindole; DSS: dextran sulfate sodium; GFP: green fluorescent protein; HAI: histological activity index; IFNG/IFN-γ: interferon gamma; IL10: interleukin 10; IL1RN/IL-1Rra: interleukin 1 receptor antagonist; KD: knockdown; miRNA: microRNA; MSCs: mesenchymal stem cells; MSCT: mesenchymal stem cell transplantation; NTA: nanoparticle tracking analysis; PGE2: prostaglandin E2; SD: standard deviation; siRNA: small-interfering RNA; STAT3: signal transducer and activator of transcription 3; TEM: transmission electron microscopy; TGFB1/TGF-β1: transforming growth factor, beta 1; Th17 cell: T helper cell 17; TNF/TNF-α: tumor necrosis factor; TNFAIP6/TSG6: tumor necrosis factor alpha induced protein 6; Tregs: regulatory T cells